2021
DOI: 10.3390/info12020068
|View full text |Cite
|
Sign up to set email alerts
|

Culture and Society in the Digital Age

Abstract: This paper aims to examine a theoretical framework of digital society and the ramifications of the digital revolution. The paper proposes that more attention has to be paid to cultural studies as a means for the understanding of digital society. The approach is based on the idea that the digital revolution’s essence is fully manifested in the cultural changes that take place in society. Cultural changes are discussed in connection with the digital society’s transformations, such as blurring the distinction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 23 publications
1
23
0
2
Order By: Relevance
“…This is all the more true in modern society, where “the most important condition of existence is not our knowledge but our attention” [ 34 ]. One of its main features may be the shift from information scarcity to abundance, but information abundance competes for limited collective attention [ 35 ].…”
Section: Changing Conditions Of Chemistry Communicationmentioning
confidence: 99%
“…This is all the more true in modern society, where “the most important condition of existence is not our knowledge but our attention” [ 34 ]. One of its main features may be the shift from information scarcity to abundance, but information abundance competes for limited collective attention [ 35 ].…”
Section: Changing Conditions Of Chemistry Communicationmentioning
confidence: 99%
“…Moreover, these platforms also allow online freelancers to properly brand themselves in the niche that they want to pursue. The study by Levin and Malmok (2021) found that the accessibility of communication platforms and digital technologies are parts of the cultural change people experience in this age. Such technologies reform, reshape, and disrupt human behaviors (Yampolskiy, 2020).…”
Section: Effect Of Digital Technologies Support On Cultural and Socia...mentioning
confidence: 99%
“…Interactivity that provides by internet as a media has brought a new way of communication among people in a society, and by all means its culture. Levin and Mamlok (2021) states that the digital age signifies the transition to what we described as the technological culture (p. 11).…”
Section: Digital Age and The Information Societymentioning
confidence: 99%